Composting of food and yard wastes by locally isolated fungal strains - Adebayo, Opatokun; Kabbashi, Nassereldeen; Alam, Md. Zahangir; Salihu, Aliyu; Abass O., Alade; Tijani, I. R. D (2011)
Three lignocellulolytic isolates of filamentous fungi Phanerochaete chrysosporium PC-13 (PC2094), Lentinus Tigrinus M609RQY (IMI 398363), Aspergilus niger and Penicillium spp. were used as inocula in combination with source separated organics (Food and Yard trimmings) from Institutional Solid Waste (ISW) to produce biofertilizer and stabilize wastes constituents. The results demonstrated that composting with sequential pure culture accelerates substrates decomposition and reduce the bulk volume. The moisture content was 64%, and the percentage C/N decreased ranged between 4.73 and 7.60% while the produced compost C/N ratio was 16%, indicating its viability for large-scale production since the acceptable range for efficient compost is between ˃12%. The 74% Total Organic Matter (TOM), 7.2 pH and 117% Germination Index (GI) further showed the potentials of the compost. Based on this, FW and YM showed an economic potential for sustainable production of compost using low technology.